IMPLENTASI MANAJEMEN WAKTU DAN KEHIDUPAN BERASRAMA TERHADAP KEDISIPLIAN TARUNA DALAM DINAS JAGA - Wirza, Elfira; AL-Bana, Muhammad Hasan (JURNAL SAINS DAN TEKNOLOGI MARITIM, 2026)
This study was motivated by the importance of discipline among cadets while performing guard duty in a maritime vocational education environment, where time management and dormitory conditions are considered dominant factors influencing disciplinary behavior. The main objective of this study was to evaluate the extent to which time management and dormitory conditions contribute to the level of discipline among cadets while performing guard duty at the West Sumatra Maritime Polytechnic. This study uses an explanatory method with a quantitative approach. All cadets were included in the population, while sampling was conducted randomly to obtain 100 respondents. The main data were collected through a structured questionnaire and analyzed using multiple linear regression, accompanied by validity and reliability tests, F-tests, t-tests, and coefficient of determination analysis. The findings show that time management has a positive and significant effect on cadet discipline, with a regression coefficient of 0.195 and a significance of 0.035. In addition, the dormitory environment also has a significant positive effect, with a regression coefficient of 0.241 and a significance of 0.000. The F test results show a significance of 0.000, indicating that both independent variables simultaneously affect cadet discipline. The adjusted R² value of 0.971 indicates that 97% of the variation in cadet discipline is explained by these two factors, while the remaining 3% is influenced by other factors outside the model. The practical implication is that strengthening time management training and dormitory guidance is very important in shaping cadet discipline.